Transverse Colon Perforation in a Patient with Primary Systemic Amyloidosis Associated with Multiple Myeloma - Justin Zelones; Divya Sood; Sonia L. Ramamoorthy (Surgical Research – Open Journal, 2015)
Amyloidosis is caused by extracellular deposits of amyloid by plasma cells, which can be idiopathic, occur with chronic inflammatory conditions, familial, or be associated with Multiple Myeloma. The Gastrointestinal tract can be affected by amyloidosis and can lead to colonic perforation, which is a rare cause of Gastrointestinal perforation as there are only nine cases documented in the literature. The aim of this case report is to describe a patient presenting with a colon perforation secondary to amyloidosis associated with Multiple Myeloma. A 66 year old male presented with diffuse abdominal pain, distention, and obstipation. Imaging demonstrated free air so he was taken to the operating room for a subtotal colectomy and end ileostomy for a transverse colon perforation. Pathology was consistent with amyloidosis in the colon. Further workup revealed that he had multiple organ systems affected by amyloid deposits along with Multiple Myeloma. Given his cardiac involvement by amyloidosis he succumbed to the disease four weeks after diagnosis. In the setting of bowel perforation and multi-organ failure of unknown etiology it is important to keep protein deposition diseases such as amyloidosis in the differential diagnosis.